2016
DOI: 10.1002/acp.3282
|View full text |Cite
|
Sign up to set email alerts
|

Impromptu Decisions to Deceive

Abstract: This research furthers understanding of the factors that induce individuals to choose deception. Its goals were to expand and test a recent account of the cognition of deception, Activation-Decision-Construction-Action Theory (ADCAT), in a mock job interview inviting impromptu deception. Decisions to lie are hypothesized to depend on the truth and other information activated from long-term memory by the social context. Activated information then guides evaluation of the likely costs of truth telling and benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…It was also the first study to look at how reason to lie can affect this decision-making process. In support of Walczyk et al (2016) and Masip et al (2016), positive associations were found between calculated motivation to lie and expecting to decide to lie. Additionally, we found a positive relationship between the EV of lying and deciding to lie, in line with Walczyk et al (2016), but contrary to Masip et al (2016).…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…It was also the first study to look at how reason to lie can affect this decision-making process. In support of Walczyk et al (2016) and Masip et al (2016), positive associations were found between calculated motivation to lie and expecting to decide to lie. Additionally, we found a positive relationship between the EV of lying and deciding to lie, in line with Walczyk et al (2016), but contrary to Masip et al (2016).…”
Section: Discussionmentioning
confidence: 81%
“…In support of Walczyk et al (2016) and Masip et al (2016), positive associations were found between calculated motivation to lie and expecting to decide to lie. Additionally, we found a positive relationship between the EV of lying and deciding to lie, in line with Walczyk et al (2016), but contrary to Masip et al (2016). We also found that a negative relationship between the EV of truth-telling and expecting to decide to lie only occurred when the lie was otheroriented.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations